(untitled) (Annals of Medical Research, 2021)
Aim: Hip joint replacement provides a dramatic improvement in the quality of life of patients with hip arthrosis but this effect has not been fully achieved in young patients because of early failure with total hip arthroplasty with high activity level. A bone mass protective procedure such as hip resurfacing arthroplasty might be advantageous in young patients. Many options for hip resurfacing prosthesis are available. One of the most used is the Birmingham hip resurfacing prosthesis. The purpose of this investigation compared retrospectively the functional, clinical and radiological outcomes of patients who underwent Birmingham hip resurfacing arthroplasty by a single surgeon for various hip arthrosis.Materials and Methods: Twenty-six hips of 22 patients (12 male, 10 female) were evaluated by using Harris hip score preoperatively and postoperatively. Anteroposterior, lateral and cross-table lateral radiographs of the pelvis and hips were evaluated with respect to component position, migration, and radiolucency postoperatively and at every follow up. Acetabular inclination and anteversion angle, implant-femoral shaft angle, varus and valgus positon, pseudotumor formation around the hip were evaluated by radiologist. Blood samples of patients were taken at last follow ups and evaluated for cobalt and chromium levels by using an inductively-coupled plasma mass spectrometer. Results: Postoperative Harris hip scorewas found to be significantly higher than preoperative Harris hip score. Correlation between chromium ion and size of femoral component, cobalt ion and cup anteversion angle had inverse relationship. There was significant correlation between cobalt ion and gender; females had higher levels of cobalt ion than males.Conclusion: In order to avoid ion load in Birmingham hip resurfacing, caution in selection of patients, avoidance of the use of small components, and attention to the surgical technique to ensure proper placement of the component angles are crucial.